Peran Vital Jurnalisme Warga dalam Pemulihan Pasca Bencana Tanah Longsor di Cianjur - Erti Fadhilah Putri (Jagratara: Journal of Disaster Research, 2023)
This research discusses the crucial role of citizen journalism in the context of landslide disaster risk in Cianjur by applying a qualitative approach and analytical descriptive research methods. The results of the in-depth analysis highlight the importance of citizen journalism in empowering local communities with actual information, mobilizing support, and building solidarity in crisis situations. Although several hyperlocal social media accounts provide information, the involvement of citizen journalists in covering and informing post-disaster conditions is still minimal. In the context of mitigation and recovery, citizen journalism can play an important role in conveying local perspectives, monitoring the environment, and responding to specific community needs that may otherwise be overlooked. Evaluation of the impact, challenges and opportunities of citizen journalism in dealing with the landslide disaster in Cianjur is important to holistically understand its role and potential contribution in strengthening the sustainability and resilience of communities in the future.